2005
DOI: 10.1158/0008-5472.can-05-1925
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glycogen Synthase Kinase 3β Disrupts the Binding of Hexokinase II to Mitochondria by Phosphorylating Voltage-Dependent Anion Channel and Potentiates Chemotherapy-Induced Cytotoxicity

Abstract: Transformed cells are highly glycolytic and overexpress hexokinase II (HXK II). HXK II is capable of binding to the mitochondria through an interaction with the voltagedependent anion channel (VDAC), an abundant outer mitochondrial membrane protein. The binding of HXK II to mitochondria has been shown to protect against loss of cell viability. Akt activation inhibits apoptosis partly by promoting the binding of HXK II to the mitochondria, but the mechanism through which Akt accomplishes this has not been chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
353
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(367 citation statements)
references
References 46 publications
(45 reference statements)
9
353
2
3
Order By: Relevance
“…It has been reported that GSK3β could interact with ANT at the inner mitochondrial membrane in the heart 9 and/or to phosphorylate voltage-dependent anion channel (VDAC) and cyclophilin D (CypD) in cancer cells. 10,11 GSK3β also has other proposed mechanisms of action, including a poorly characterized role in calcium (Ca 2+ ) homeostasis regulation 12 and protein-protein interactions, 9 as well as functions in different subcellular fractions such as the nucleus, cytosol and mitochondria. 13 Reperfusion is the most powerful intervention to salvage ischemic myocardium.…”
mentioning
confidence: 99%
“…It has been reported that GSK3β could interact with ANT at the inner mitochondrial membrane in the heart 9 and/or to phosphorylate voltage-dependent anion channel (VDAC) and cyclophilin D (CypD) in cancer cells. 10,11 GSK3β also has other proposed mechanisms of action, including a poorly characterized role in calcium (Ca 2+ ) homeostasis regulation 12 and protein-protein interactions, 9 as well as functions in different subcellular fractions such as the nucleus, cytosol and mitochondria. 13 Reperfusion is the most powerful intervention to salvage ischemic myocardium.…”
mentioning
confidence: 99%
“…Another, more specific approach is based upon the observation that a chimeric protein containing the 15 amino-terminal hydrophobic residues of HKI binds to mitochondria and can be specifically displaced by the addition of increasing amounts of HKI (Gelb et al, 1992). Subsequent studies have demonstrated that incubating cells with cell-permeable peptides corresponding to or containing the amino-terminal hydrophobic domains of mitochondrial hexokinases are capable of competitively displacing endogenous hexokinases from mitochondria in intact cells and sensitizing them to apoptosis at a level upstream of cytochrome c release (Pastorino et al, 2002(Pastorino et al, , 2005Majewski et al, 2004a) (N Hay and RB Robey, unpublished observations). So how do mitochondrial hexokinases inhibit apoptosis and maintain OMM integrity?…”
Section: Mitochondrial Hexokinases As Downstream Effectors Of Growth mentioning
confidence: 99%
“…In principle, Akt could also indirectly influence this interaction through Aktmediated changes in the activity of downstream effectors capable of modifying hexokinase or VDAC in a manner that influences their interaction. Such a demonstration has not been made for hexokinase, but it has been suggested that GSK3b, which is phosphorylated and inhibited by Akt, can disrupt mitochondrial hexokinase association via phosphorylation of a putative hexokinase docking site on VDAC (Pastorino et al, 2005). This site is in close proximity to the critical glutamate residue covalently modified by DCCD and suggests at least one mechanism whereby Akt, through direct phosphorylation and inactivation of GSK3b, could augment mitochondrial hexokinase interaction and promote cell survival.…”
Section: How Do Growth Factors and Akt Mediate Hexokinase-mitochondrimentioning
confidence: 99%
“…[18][19][20][21] Hexokinases I and II (HK-I and HK-II) have mitochondrialbinding motifs and these enzymes have been demonstrated to localize at mitochondria as well as in cytosol. 13,22 A role for hexokinase in mitochondrial protection was recently reported. [22][23][24][25][26] Interestingly the ability of Akt to protect against cytochrome c release and apoptosis in fibroblasts was shown to be decreased by HK-II dissociation from mitochondria.…”
mentioning
confidence: 99%
“…12 GSK3b, another substrate for Akt, has also recently been reported to contribute to mitochondrial protection mediated by Akt. 13 Several lines of evidence demonstrate that cardiomyocyte injury induced by ischemia/reperfusion results from increased cytosolic Ca 2 þ and generation of reactive oxygen species, which subsequently leads to mitochondrial depolarization and initiates a cell death cascade. 2,14,15 Ischemic injury and oxidative stress disrupt mitochondrial integrity through opening of a mega channel referred to as the permeability transition (PT) pore.…”
mentioning
confidence: 99%